Evaluation of the mining formal activity in Oyón, years 2007 – 2017 - Bobbio Rosas, Emilio Gustavo Arturo Sandro Edmundo (2023)
Formal mining in Oyón, Lima Region, is evaluated: the damages and benefits caused to water, soil and the population, its profits and what is delivered to the country by the Uchucchacua Mining Unit. It includes the analysis of what it contributes to the National Budget and to the Provincial and District Municipalities (economic, objective impact), the feeling of the population (social, subjective impact, perception), the effects of its actions on the environment (environmental impact, objective) and what is obtained by the company (economic profits, objective). There is an additional impact on subsidiary activities, basically suppliers, but in any case, given that the manufacturers of the really expensive mining equipment are foreign companies and the complexity of this analysis, it has been discarded, since it would be minimal for the country. There is an impact in terms of decreased unemployment, but mining does not require a large amount of labor, so it is simply indicated in figures. We collected soil and water samples and these were analyzed in the laboratory of the Agrarian University, finding contaminated soil and water. The studied financial reports showed minimal profits for Peru in relation to what was obtained by the company.